2017
DOI: 10.1038/s41467-017-00433-7
|View full text |Cite
|
Sign up to set email alerts
|

Tbx3-dependent amplifying stem cell progeny drives interfollicular epidermal expansion during pregnancy and regeneration

Abstract: The skin surface area varies flexibly in response to body shape changes. Skin homeostasis is maintained by stem cells residing in the basal layer of the interfollicular epidermis. However, how the interfollicular epidermal stem cells response to physiological body shape changes remains elusive. Here, we identify a highly proliferative interfollicular epidermal basal cell population in the rapidly expanding abdominal skin of pregnant mice. These cells express Tbx3 that is necessary for their propagation to driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…In murine proliferating epidermal tissue, two proteins secreted by dermal cells; secreted frizzled‐related protein 1 (Sfrp1) and insulin‐like growth factor‐binding protein 2 (Igfbp2) induce the proliferation of basal and progenitor epidermal cells. A similar effect has been observed by blocking the secretion of Wnt signals 52 . In post‐larval zebrafish, the observed high levels of cell proliferation may cause overcrowding, which translates into mechanical forces producing cell shape changes.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In murine proliferating epidermal tissue, two proteins secreted by dermal cells; secreted frizzled‐related protein 1 (Sfrp1) and insulin‐like growth factor‐binding protein 2 (Igfbp2) induce the proliferation of basal and progenitor epidermal cells. A similar effect has been observed by blocking the secretion of Wnt signals 52 . In post‐larval zebrafish, the observed high levels of cell proliferation may cause overcrowding, which translates into mechanical forces producing cell shape changes.…”
Section: Discussionsupporting
confidence: 63%
“…A similar effect has been observed by blocking the secretion of Wnt signals. 52 In post-larval zebrafish, the observed high levels of cell proliferation may cause overcrowding, which translates into mechanical forces producing cell shape changes. In monolayer epithelial tissues, overcrowding results in cell extrusion, which is essential to maintain homeostatic cell numbers.…”
Section: The Role Of Stem and Progenitors Cells During Epidermal Stmentioning
confidence: 99%
“…S5F), indicating that VEGFR2 signaling acts mainly in vasculatures. In addition, Tbx3 + -BCs emerged during wound healing in WT mice (16), which were significantly decreased in angiogenesis-defective VE-cadherin-creERT2;VEGFR2 flox/flox (VEGFR2 cKO) mice ( Fig. 4, P and Q, and fig.…”
Section: Tbx3 + -Bcs Are Induced By Vasculaturesmentioning
confidence: 95%
“…In addition, recent studies of single-cell transcriptomes in both murine and human epidermis have revealed multiple IFE basal cell (BC) clusters on the basis of their transcriptional heterogeneity (12)(13)(14)(15). Beyond homeostasis and wound repair, we have shown that the epidermal basal layer of rapidly expanding abdominal skin of pregnant mice harbors highly proliferating IFESC progeny that expresses T-box3 (Tbx3) necessary for their proliferation and skin expansion (16).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, p21 and p27 (cyclindependent kinase inhibitors) knockout studies in the mouse hematopoietic cells indicate that p21 specifically regulates stem cell cycle kinetics, whereas p27 regulates TA cell cycle kinetics (Cheng et al, 2000a(Cheng et al, , 2000b. Despite such differences, the division rates of stem cells and transit amplifying pool are often altered in a coordinated fashion by hormonal stimulation (Giraddi et al, 2015), tissue damage (Lehrer et al, 1998;Ichijo et al, 2017), and aging (Charruyer et al, 2009). A concerted analysis of the cell cycle regulation in stem cells and at different stages of subsequent TA is required to uncover the correlation and consequence of the stage-wise alterations of cell division rates on tissue growth and differentiation.…”
mentioning
confidence: 99%